EFFECT OF TWO ACTIVATED BLEACHING TECHNIQUES ON SURFACE ROUGHNESS OF DIFFERENT ESTHETIC RESTORATIVE MATERIALS - Tuncay Alptekın; Özgün Yusuf Özyılmaz; Filiz Aykent; Haluk Barış Kara (Cumhuriyet University, 2017)
Objectives: The aim of this in vitro study was to evaluate surface roughness of six different restorative materials during office bleaching procedures with blue light emitted diode (LED) and diode laser photo activation. Materials and Methods: Filtek TM supreme, Tetric Evo Ceram, Tescera ATL, Clearfill Majesty Esthetic, Durafill VS and IPS Empress 2 materials were evaluated in this study. Twenty specimens, 10 mm in diameter and 2 mm thick, were fabricated from each material using a teflon mold. All specimens were randomly assigned to two groups (n=10). Group 1 received two topical applications of 35% hydrogen peroxide for 20 s. And was photoactivated using LED. Group 2 received topical application of 46% hydrogen peroxide using diode laser. Surface roughness values were measured prior to and following bleaching procedures by using a profilometer. Data were analyzed statistically, by one-way-analysis of variance (ANOVA), post-hoc Tamhane's T2 and independent t tests. Results: Surface roughness values for all restorative materials tested increased after both bleaching procedures (p<0.05). Tescera ATL bleached with diode laser photo activation showed higher surface roughness value than LED activation (p<0.05). However, there were no significant differences in two bleaching methods for other restorative materials (p>0.05). Conclusions: Although clinical effects depend on in-vivo conditions, the effects of office bleaching agents should be known and applied cautiously when a colored restoration is bleached or a restoration is neighboured with the tooth bleached. Keywords: Esthetic restorative materials, Dental porcelain, Teeth bleaching, Surface roughness, Semiconductor lasers